2009
DOI: 10.1152/japplphysiol.00532.2009
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent mobilization of circulating progenitor cells during strenuous exercise in healthy individuals

Abstract: Exercise stimulates the release of hematopoietic and endothelial progenitor cells (EPC) from the bone marrow. However, no data are available concerning the time frame of EPC release during strenuous exercise. The aim of the present study was to investigate the time-dependent release of progenitor cells during strenuous exercise. Eighteen healthy young men cycled for 4 h continuously at 70% of their individual anaerobic threshold. Peripheral blood was drawn at 16 predefined time points during and after finishin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
146
6
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 50 publications
(62 reference statements)
10
146
6
4
Order By: Relevance
“…Thus, Strong physical exercise, as the ones performed by marathoners, did not present any alteration in the EPC concentration 28 , while a recent study published by Goussetis et al 29 demonstrated increase of 10 times of the EPC after 246 km of foot race and that his mobilization mediated by exercise was associated with the release of VEGF in the circulation. Similarly to this study, Möbius-Winkler et al 30 showed EPC increase in the circulation of healthy individuals from the 210 min of strong exercise, indicating hence increase of these cells which depend on the time of performance of the exercise.…”
Section: Measurement Of the Citrate Synthase Enzyme Activitysupporting
confidence: 86%
“…Thus, Strong physical exercise, as the ones performed by marathoners, did not present any alteration in the EPC concentration 28 , while a recent study published by Goussetis et al 29 demonstrated increase of 10 times of the EPC after 246 km of foot race and that his mobilization mediated by exercise was associated with the release of VEGF in the circulation. Similarly to this study, Möbius-Winkler et al 30 showed EPC increase in the circulation of healthy individuals from the 210 min of strong exercise, indicating hence increase of these cells which depend on the time of performance of the exercise.…”
Section: Measurement Of the Citrate Synthase Enzyme Activitysupporting
confidence: 86%
“…Physical exercise has been shown to increase the function and number of circulating EPCs in healthy individuals (Hoetzer et al, 2007;Yang et al, 2007;Mö bius-Winkler et al, 2009;Walther et al, 2009;Witkowski et al, 2010), which is paralleled with improvement of endothelial function. However, it is not clear whether exercise contributes to the promotion of endothelial repair capacity of EPCs from elderly men and if yes, whether CXCR4 ⁄ JAK-2 signaling is involved in the functional regulation of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Is it therefore acceptable to assume that a single bout of exercise is sufficient to induce an EPC-mediated vascular protection? For this discussion it is important to realize that the amount of circulating progenitors after a single exercise bout declines immediately back to baseline values (2,55). Regular physical activity on the other hand leads to elevated circulating EPC levels over a longer time period (69).…”
Section: Single Exercise Bout Vs Exercise Training Programmentioning
confidence: 99%